Flow Cytometry-Based Assay to Identify A Competent Embryo in FET Cycles - Akcay, Berkay; Meric, Neslihan; Olcay, I Orcun; Ergun, Yagmur; Boynukalin, Kubra; Arici, Aydin; Bahceci, Mustafa; Basar, Murat (Archives of Clinical and Biomedical Research, 2023)
Objectives: We aimed to investigate a non-invasive selection method to predict competent embryos before frozen-thawed embryo transfer. Methods: Fifty-three random infertile patients undergoing a frozenthawed embryo transfer cycle at Bahceci Health Group Umut IVF Laboratory, Istanbul, were included in the study. Fifty-three patients’ embryos were thawed and cultured before transfer (100-120 min). Spent culture media was evaluated through flow cytometry for the PI (+) EV percentage. Results: Spent culture media with a lower percentage of PI (+) EVs were significantly higher implantation rates compared to higher PI+ EVs percentages (respectively; 4.18 ± 0.33, 7.9 ± 0.62; p<0.0001). Plotting data of confirmed competent embryos versus data from implantation failure yielded a 4.71% PI (+) EV count cut-off, corresponding to a maximum specificity and sensitivity. The AUC (area under the curve) was 0.888 (95% CI: 0.801–0.975). Conclusion: Our result demonstrates that a PI (+) EV presence threshold in spent culture media can predict a healthy pregnancy outcome for frozen embryo transfer.